Low proportion of unreported cervical treatments in the cancer registry of Norway between 1998 and 2013. (2nd December 2018) - Leinonen, Maarit K.; Hansen, Svenn A.; Skare, Gry Baadstrand; Skaaret, Inger Berit; Silva, Monica; Johannesen, Tom Børge; Nygård, Mari
Abstract: Background: Accurate information about treatment is needed to evaluate cervical cancer prevention efforts. We studied completeness and validity of reporting cervical treatments in the Cancer Registry of Norway (CRN). Material and methods: We identified 47, 423 (92%) high-grade cervical dysplasia patients with and 3983 (8%) without recorded treatment in the CRN in 1998–2013. We linked the latter group to the nationwide registry of hospital discharges in 1998–2015. Of patients still without treatment records, we randomly selected 375 for review of their medical history. Factors predicting incomplete treatment records were assessed by multiple imputation and logistic regression. Results: Registry linkage revealed that 10% (401/3983) of patients received treatment, usually conization, within one year of their initial high-grade dysplasia diagnosis. Of those, 11% ( n  = 44) were missing due to unreporting and 89% ( n  = 357) due to misclassification at the CRN. Of all cases in medical review, patients under active surveillance contributed almost 60% (223/375). Other reasons of being without recorded treatment were uncertain dysplasia diagnosis, invasive cancer or death. Coding error occurred in 19% (73/375) of randomly selected cases. CRN undercounted receipt of treatment by 38% ( n  = 1526) among patients without recorded treatment which translates into 97% overall completeness of treatment data. Incomplete treatment records were particularly associated with public laboratories, patients aged 40–54 years, and the latest study years. Conclusions: CRN holds accurate information on cervical treatments. Completeness and particularly validity can be further improved through the establishment of new internal routines and regular linkage to hospital discharges.